Full Chromosomal Relationships Between Populations and the Origin of Humans - Dong, Rui; Pei, Shaojun; Guan, Mengcen; Yau, Shek-Chung; Yin, Changchuan; He, Rong L.; Yau, Stephen S.-T. (Frontiers in Genetics, 2022)
A comprehensive description of human genomes is essential for understanding human evolution and relationships between modern populations. However, most published literature focuses on local alignment comparison of several genes rather than the complete evolutionary record of individual genomes. Combining with data from the 1000 Genomes Project, we successfully reconstruct 2504 individual genomes and propose Divided Natural Vector method to analyze the distribution of nucleotides in the genomes. Comparisons based on autosomes, sex chromosomes and mitochondrial genomes reveal the genetic relationships between populations, and different inheritance pattern leads to different phylogenetic results. Results based on mitochondrial genomes confirm the “out-of-Africa” hypothesis and assert that humans, at least females, most likely originated in eastern Africa. The reconstructed genomes are stored on our server and can be further used for any genome-scale analysis of humans (temporary link for editors and reviewers: http://yaulab.math.tsinghua.edu.cn/Frontiers/). This project provides the complete genomes of thousands of individuals and lays the groundwork for genome-level analyses of the genetic relationships between populations and the origin of humans.